Gas Sensors 1992
DOI: 10.1007/978-94-011-2737-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Gas Sensors Based on SnO2 Thick Films

Abstract: ABSTRACT. Some physical and chemical aspects about the behaviour of semiconductor gas sensors are discussed. Discussion is restricted to sintered Sn02 which is usually in the form of a thick film. Since we have concentrated on electrical studies of the response characteristics of Sn02 thick films in our laboratory, the discussion also has an emphasis on the transducing properties (conductance signals) of the sensor. Initially, some electrical properties of Sn02 are reviewed. Subsequently a description of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 87 publications
0
12
0
1
Order By: Relevance
“…This organometallic complex then appears as a convenient potential precursor for the doping of tin nanoparticles, and we observed indeed that [Pt 2 (dba) 3 ] also decomposed in the presence of colloidal tin/tin oxide nanoparticles suspended in anisole, when exposed to 1 atm of carbon monoxide.…”
Section: Synthesis and Characterization Of [Sn/sno X /Pt] Nanoparticlesmentioning
confidence: 60%
See 4 more Smart Citations
“…This organometallic complex then appears as a convenient potential precursor for the doping of tin nanoparticles, and we observed indeed that [Pt 2 (dba) 3 ] also decomposed in the presence of colloidal tin/tin oxide nanoparticles suspended in anisole, when exposed to 1 atm of carbon monoxide.…”
Section: Synthesis and Characterization Of [Sn/sno X /Pt] Nanoparticlesmentioning
confidence: 60%
“…We recently demonstrated that the reaction of [Pt 2 (dba) 3 ] with carbon monoxide in THF leads to the formation of well crystallized platinum nanoparticles of uniform size centred near 1.2 nm 41 which can be easily functionalized through coordination of various ligands at their surface. This organometallic complex then appears as a convenient potential precursor for the doping of tin nanoparticles, and we observed indeed that [Pt 2 (dba) 3 ] also decomposed in the presence of colloidal tin/tin oxide nanoparticles suspended in anisole, when exposed to 1 atm of carbon monoxide.…”
Section: Synthesis and Characterization Of [Sn/sno X /Pt] Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations